A Clinical Study to Evaluate the Efficacy of Kutaj Kshar Sutra Using IFTAK Technique in the Management of Bhagandara (Complex Fistula in Ano) (AYUSHDHARA, 2025)
Bhagandara (complex fistula-in-ano) is a challenging anorectal disorder with high recurrence rates and significant morbidity. Conventional surgical approaches often result in complications such as incontinence and delayed wound healing. Ayurveda offers a promising alternative through Kshar Sutra therapy, which is known for its minimal recurrence and effective fistula healing. Kutaj (Holarrhena antidysenterica) Kshar Sutra is a specialized medicated thread that has potent antimicrobial, anti-inflammatory, and wound-healing properties. Objective: This clinical study aims to evaluate the efficacy of Kutaj Kshar Sutra using the IFTak (Interception of Fistulous Tract and Application of Kshar Sutra) technique in the management of Bhagandara (complex fistula-in-ano). Methodology: A controlled clinical trial was conducted on patients diagnosed with complex fistula in ano. Participants were treated with the IFTak technique, wherein the fistulous tract was intercepted and Kutaj Kshar Sutra was applied. Patients were monitored for parameters such as pain relief, healing time, recurrence rate, and complications. Results: Preliminary findings suggest that the Kutaj Kshar Sutra with the IFTak technique leads to faster healing, reduced recurrence, and better postoperative outcomes compared to conventional surgical methods. The natural caustic and antibacterial properties of Kutaj Kshar enhance the healing process while minimizing tissue damage. Conclusion: The study highlights the effectiveness of Kutaj Kshar Sutra using the IFTak technique as a viable and safe alternative in the management of complex fistula in ano. It offers a minimally invasive, cost-effective, and recurrence-free approach with improved patient outcomes. Further large-scale studies are recommended to validate these findings.